An algorithm recommendation for the management of knee osteoarthritis in Europe and internationally: A report from a task force of the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO) - Bruyère, Olivier; Cooper, Cyrus; Pelletier, Jean-Pierre; Branco, Jaime; Luisa Brandi, Maria; Guillemin, Francis; Hochberg, Marc C.; Kanis, John A.; Kvien, Tore K.; Martel-Pelletier, Johanne; Rizzoli, René; Silverman, Stuart; et al. (Seminars in arthritis and rheumatism, 2014)
Existing practice guidelines for osteoarthritis (OA) analyze the evidence behind each proposed treatment but do not prioritize the interventions in a given sequence. The objective was to develop a treatment algorithm recommendation that is easier to interpret for the prescribing physician based on the available evidence and that is applicable in Europe and internationally. The knee was used as the model OA joint. ESCEO assembled a task force of 13 international experts (rheumatologists, clinical epidemiologists, and clinical scientists). Existing guidelines were reviewed; all interventions listed and recent evidence were retrieved using established databases. A first schematic flow chart with treatment prioritization was discussed in a 1-day meeting and shaped to the treatment algorithm. Fine-tuning occurred by electronic communication and three consultation rounds until consensus. Basic principles consist of the need for a combined pharmacological and non-pharmacological treatment with a core set of initial measures, including information access/education, weight loss if overweight, and an appropriate exercise program. Four multimodal steps are then established. Step 1 consists of background therapy, either non-pharmacological (referral to a physical therapist for re-alignment treatment if needed and sequential introduction of further physical interventions initially and at any time thereafter) or pharmacological. The latter consists of chronic Symptomatic Slow-Acting Drugs for OA (e.g., prescription glucosamine sulfate and/or chondroitin sulfate) with paracetamol at-need; topical NSAIDs are added in the still symptomatic patient. Step 2 consists of the advanced pharmacological management in the persistent symptomatic patient and is centered on the use of oral COX-2 selective or non-selective NSAIDs, chosen based on concomitant risk factors, with intra-articular corticosteroids or hyaluronate for further symptom relief if insufficient. In Step 3, the last pharmacological attempts before surgery are represented by weak opioids and other central analgesics. Finally, Step 4 consists of end-stage disease management and surgery, with classical opioids as a difficult-to-manage alternative when surgery is contraindicated. The proposed treatment algorithm may represent a new framework for the development of future guidelines for the management of OA, more easily accessible to physicians.